IDENTIFIKASI KEANEKARAGAMAN JENIS-JENIS ANGGREK (Orchidaceae) DI HUTAN LINDUNG DESA AJAOBAKI, KECAMATAN MOLLO UTARA, KABUPATEN TIMOR TENGAH SELATAN, PROVINSI NUSA TENGGARA TIMUR - Salomo Chrismondus Lasa; Maria M. E. Purnama; Mamie E Pelondo'u (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
This research was conducted to determine the diversity of types of orchids (Orchidacea). This research was carried out in the Protected Forest of Ajaobaki Village, North Mollo Sub-District, South Central Timor Regency, East Nusa Tenggara Province. It was carried out for 1 month, from July to August 2020. This study used purposive sampling, survey and transect pathway methods. Data analysis used qualitative descriptive analysis and quantitative descriptive analysis. The data were processed using the Shannon Wiener diversity index formula (H '). The results showed that there were 10 types of epiphytic orchids found in the sampling plot in the protected forest of Ajaobaki Village. The most common orchids found were Dendrobium secundum as many as 569 species and the least was Lipariscrenulata with 2 species. There are 3 types of trees recorded, namely Ampupu (Eucalyptus urophylla), Cemara (Casuarina junghuniana), and Mahogany (Swietenie mahagoni). Protected forest areas have homogeneous forest types, which has the most tree types that are mostly dominated by Pine trees (Casuarina junghuniana). The host tree for orchids that is more dominant as the attachment for orchids is the Pine tree (Casuarina junghuniana). The results of the calculation of the diversity of orchids on the observation plot were calculated using the Shannon winner index of 1.87 (H '). The diversity types of orchid (Orchidacea) in the protected forest of Ajaobaki Village having moderate diversity (1≤H’≤3) because there is a lot of orchid theft and also taking firewood in the Protected Forest so that there are fewer orchids.